EVOLUTION TOWARDS FREEDOM: SUN GOKONG AS A SYMBOL OF HUMAN BEHAVIORAL TRANSFORMATION AS INSPIRATION FOR SCULPTURE CREATION AT THE LABDA SCULPTURE STUDIO - Frasnanda, Nyoman Ferry; Bendi Yudha, I Made; Mustika, I Ketut (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
This study aims to create a series of sculptures that represent the philosophical concept of freedom through the symbolic transformation of human behavior, using the character of Sun Gokong as the central figure. The research adopts a practice-based approach combining additive and subtractive sculpting techniques. Various materials, including aluminum wire, resin, gypsum, and clay, were used to construct six sculptures representing stages of human development from primitive existence to spiritual awareness. The results demonstrate that the sculptural series visualizes a gradual transformation of human consciousness, from instinctive behavior to rational and spiritually mature conditions. The final sculpture depicting Sun Gokong symbolizes the attainment of self-control and inner liberation. This study confirms that sculpture can function not only as an aesthetic object but also as a medium for philosophical reflection on human transformation and the meaning of freedom in contemporary life.